2003
DOI: 10.1242/dev.00213
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of distinct neurogenic and melanogenic neural crest sublineages

Abstract: Clonal and lineage analyses have demonstrated that although some neural crest cells have the ability to generate multiple cell types and display self-renewal ability, other crest cells generate a single or limited repertoire of cell types. However, it is not yet clear when, and in what order, crest cells become specified to adopt a particular fate. We report that the receptor tyrosine kinases TrkC and C-Kit are expressed by distinct neural crest subpopulations in vitro. We then analyzed the lineages of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 44 publications
5
68
3
Order By: Relevance
“…7). In contrast to our studies, an in vitro culture study using quail embryo NC cells showed that the Kitþ NC cells invariably give rise to clones containing only M (Luo et al, 2003). Additionally, an in vivo immunohistochemistry study on mouse embryos showed that the migrating Kitþ NC cells give rise to only M (Wilson et al, 2004).…”
Section: Developmental Dynamicscontrasting
confidence: 99%
See 3 more Smart Citations
“…7). In contrast to our studies, an in vitro culture study using quail embryo NC cells showed that the Kitþ NC cells invariably give rise to clones containing only M (Luo et al, 2003). Additionally, an in vivo immunohistochemistry study on mouse embryos showed that the migrating Kitþ NC cells give rise to only M (Wilson et al, 2004).…”
Section: Developmental Dynamicscontrasting
confidence: 99%
“…NC-like cells were isolated as Kit-expressing cells by flow cytometry, and they differentiated into N, G, and M, suggesting that these Kit-expressing cells have multipotency. However, in vivo Kit-expressing NCderived cells are reported to migrate dorsolaterally in the skin and differentiate only into M (Henion and Weston, 1997;Luo et al, 2003;Wilson et al, 2004). To further investigate the commitment potential of these early NClike cells, we took advantage of the Sox10 transcription factor as a wellcharacterized NC marker.…”
Section: Generation Of Sox10-iresvenus Es Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, it will be interesting to see whether eNCSCs and pigment cell precursors segregate from a truly multipotent neural crest stem cell. Such a scenario would be consistent with the identification of segregated melanocyte progenitors in mouse dorsal neural tube (Wilson et al, 2004) and early migrating NCCs from avian neural tube explants (Henion and Weston, 1997;Luo et al, 2003).…”
Section: Early Neural Crest Stem Cellssupporting
confidence: 76%